«Τι είναι το Βυζάντιο» στα ελληνικά σχολικά εγχειρίδια. Από την «Ελληνική Αυτοκρατορία» στον εγκλωβισμό μεταξύ της ύστερης αρχαιότητας και της πρώιμης νεωτερικότητας - K. Nikolaou (200 ΧΡΟΝΙΑ ΑΠΟ ΤΗΝ ΕΛΛΗΝΙΚΗ ΕΠΑΝΑΣΤΑΣΗ Αναζητώντας τη γνώση: Τα σχολικά εγχειρίδια στο Ελληνικό Κράτος, 2023)
“What is Byzantium” in Greek school textbooks. From the “Greek Empire” to the caging between late antiquity and early modernity .“Byzantium”, as a technical term, was coined in France of Louis XIV to describe the based in Constantinople eastern region of the Roman state, which was gradually transformed into the initially Greek-speaking and gradually Greek medieval empire. As a historical period but also as an object of scientific research, Byzantium was a problem or raised concerns for the transition from the world of antiquity to the modern Hellenism and the new Greek state. Therefore, it caused embarrassment as to how it was displayed and examined in school textbooks. Along with the development of historiography but often with epistemological ambivalence, the Byzantine Empire was treated with reservations, fabricated prejudices and expediencies. At other times, an attempt was made to elevate the imperial grandeur, referring to Greek glory and splendour. At other times, its history was squeezed between the “overemphasized” late antiquity and the changes and achievements of Western European modernity, depriving Byzantinology of its independence as a scientific field and Byzantium of its characteristics as a distinct historical era. The study outlines this multifaceted approach in Greek school textbooks, and highlights its points, compatible or incompatible with the evolution of Byzantine studies at international and national level.